Subjective cognitive decline in patients with Parkinson’s disease: an updated review - Huang, Juan; Yuan, Xingxing; Chen, Lin; Hu, Binbin; Jiang, Lijuan; Shi, Ting; Wang, Hui; Huang, Wei (Frontiers in Aging Neuroscience, 2023)
Cognitive impairment in patients with Parkinson’s disease (PD) worsens the prognosis of PD and increases caregivers’ burden and economic consequences. Recently, subjective cognitive decline (SCD), which refers to self-reported cognitive decline without detectable objective cognitive dysfunction, has been regarded as an at-risk state of mild cognitive impairment (MCI) and a prodromal stage for dementia in Alzheimer’s disease (AD). However, studies on PD-SCD have thus far been scarce, and at present there is no consensus regarding the definition of SCD nor a gold standard as an evaluation tool. The present review aimed to look for an association between PD-SCD and objective cognitive function and found that PD with SCD occurred with brain metabolic changes, which were consistent with early aberrant pathological changes in PD. Moreover, PD patients with SCD were likely to progress to future cognitive impairment. It is necessary to establish a guideline for the definition and evaluation of SCD in PD. A larger sample size and more longitudinal investigations are needed to verify the predictive effectiveness of PD-SCD and to detect earlier subtle cognitive decline before MCI.